2014
DOI: 10.1002/hrm.21635
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Three to Tango: Exploring the Interplay among Training Intensity, Job Autonomy, and Supervisor Support in Predicting Knowledge Sharing

Abstract: This study explored whether the relationship between perceived training intensity and knowledge sharing is prone to combined moderating infl uences. We operationalized perceived training intensity as a challenge stressor, in accordance with the challenge-hindrance framework of work stressors. The results of a study of 129 employees from three Norwegian service industries revealed a positive relationship between perceived training intensity and supervisor-rated knowledge sharing for employees reporting high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 66 publications
3
53
0
Order By: Relevance
“…Our findings, first of all, contribute to understanding more about how individuals' perceptions of HR practices influence KEC. The results indicate the positive influence of perceptions of learning‐enhancing employment practices on perceptions of KEC among knowledge workers, thereby adding to the body of prior research linking perceptions of learning‐related employment practices to knowledge sharing (Bednall et al ., ; Kuvaas et al ., ; Buch et al ., ). The results also illustrate the importance of employee‐centred HR practices that focus on the enhancement of learning in supporting the HRM‐knowledge linkage.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our findings, first of all, contribute to understanding more about how individuals' perceptions of HR practices influence KEC. The results indicate the positive influence of perceptions of learning‐enhancing employment practices on perceptions of KEC among knowledge workers, thereby adding to the body of prior research linking perceptions of learning‐related employment practices to knowledge sharing (Bednall et al ., ; Kuvaas et al ., ; Buch et al ., ). The results also illustrate the importance of employee‐centred HR practices that focus on the enhancement of learning in supporting the HRM‐knowledge linkage.…”
Section: Discussionmentioning
confidence: 97%
“…Kehoe and Wright, ). For example, studies have reported a positive relationship between perceived training intensity and knowledge sharing (Kuvaas et al ., ; Buch et al ., ). This research indicates that such training increases intrinsic and prosocial motivation to share knowledge (Kuvaas et al ., ), and that structural ( i .…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Knowledge transfer within intra or inter firm network create chances for collective learning and co-existence, leading to novel knowledge, innovative approaches and practices to augment firm performance [77]. The concept of training and development and knowledge transfer emphasizes on how firms update the skills, abilities, experience and knowledge of their workforce through training and development programs [78] to handle or support tacit or explicit knowledge transfer received, which in turn can contribute to firm innovative performance [42,79,80]. Training and development support the transformation of tacit or explicit knowledge received by providing a platform where new knowledge could be generated, developed, shared, integrated and applied towards firm innovative performance.…”
Section: Knowledge Transfer Training and Development And Innovation mentioning
confidence: 99%
“…Enabled by the technology platforms, employees' reflexivity is encouraged as they collaboratively review, discuss, alter, and build on each other's knowledge (Schippers, West, & Dawson, 2015). Provided that employees are motivated to share knowledge (Andreeva, Vanhala, Sergeeva, Ritala, & Kianto, 2017;Kuvaas, Buch, & Dysvik, 2012) and structural and relational networks support knowledge sharing (Buch, Dysvik, Kuvaas, & Nerstad, 2015), collaborative crowdsourcing can also foster employee learning (Malhotra, Majchrzak, Kesebi, & Looram, 2017).…”
mentioning
confidence: 99%